Artemether Bioavailability after Oral or Intramuscular Administration in Uncomplicated Falciparum Malaria - Silamut, Kamolrat (American Society for Microbiology, 2003)
The antimalarial activity of artemether following oral or intramuscular administration in the plasma of 15 adults with acute uncomplicated Plasmodium falciparum malaria was measured by bioassay. The peak concentrations in plasma following oral administration were higher in patients with acute illness (median, 1,905 mmol of dihydroartemisinin [DHA] equivalents per liter; range, 955 to 3,358 mmol of DHA equivalents per liter) than in patients in the convalescent phase (median, 955 mmol of DHA equivalents per liter; range, 576 to 1,363 mmol of DHA equivalents per liter), and clearance (CL/F) was lower in patients in the acute phase (1.11 liters/kg/h; range, 0.21 to 3.08 liters/kg/h) than in patients in the convalescent phase (median, 2.76 liters/kg/h; range, 1.56 to 5.74 liters/kg/h) (P ≤ 0.008). Antimalarial activity in terms of the peak concentration in plasma (C(max)) after oral administration was a median of 16 times higher than that after intramuscular administration. The ratio of the area under the plasma concentration-time curve during the first 24 h (AUC(0-24)) after oral administration of artemether to the AUC(0-24) after intramuscular administration was a median of 3.3 (range, 1 to 11) (P = 0.0001). In the acute phase, the time to C(max) was significantly shorter after oral administration (median, 1 h; range, 0.5 to 3.0 h) than after intramuscular administration (median, 8 h; range, 4 to 24 h) (P = 0.001). Intramuscular artemether is absorbed very slowly in patients with acute malaria.